Pengaruh Tingkat Pendidikan, Pelatihan Akuntansi, dan Umur Usaha terhadap Pengguna Informasi Akuntansi pada UMKM dengan Ketidakpastian Lingkungan sebagai Variabel Moderating di Kabupaten Dharmasraya - Mayroza Wiska; Jujuk Juan Colin (J-MAS (Jurnal Manajemen dan Sains), 2021)
The purpose of this study was to estimate the effect of education level, accounting training and age of business on users of accounting information in MSME with environmental uncertainty as a moderating variable in Dharmasraya Regency. The type of research used in this research is quantitative research that uses numbers and statistical calculations. Quantitative research is research whose type of data can be measured in a numerical scale (numbers). Where this study seeks to see a cause-and-effect relationship. The results showed that the level of education partially positive and significant effect on users of accounting information with tcount 2.841 > ttable 1,69. Accounting training partially has a positive and significant effect on users of accounting information with tcount 3.047 > ttable 1,69. Business age partially has a positive and significant effect on users of accounting information with tcount 3.522 > ttable 1,69. The conclusion is that the level of education, accounting training and age of business have a positive and significant effect on users of accounting information in MSME with environmental uncertainty as a moderating variable, because the values of tcount > ttable and Fcount > Ftable have a positive relationship direction